English Immersion programme and sense of nationalism: A case study of a senior high school in Indonesia - Pritz Hutabarat (Jurnal Ilmu Manajemen Sosial Humaniora (JIMSH), 2023)
The status of English as an international language (EIL) has shaped the teaching of English as a second/foreign language (ESL/EFL). In a multicultural and multi linguistic country such as Indonesia, the learning of English has created tensions amongst the people. Therefore, this study aims to investigate how learning English in an English immersion program effect student’s identity as Indonesian learners. The participants of this study were 59 secondary school and 10 teachers at an EIP school in Indonesia. The data were collected through questionnaire, semi-structured interview and field observation. The data from questionnaire was analysed using descriptive statistics and the data from interviews was analysed using thematic analysis. The findings show that there is a significant difference between how the students view their learning and their teacher’s in terms of how it effects their sense of nationalism. The teachers were concerned about the student’s attitude towards Indonesian arts and history claiming that they did not show respect to the local culture. Whereas students seem to dot aware of how their learning experience shape their identity. The study proposes a social and cultural examination of the EIP to complement the discussion about English learning process in Indonesia.